2019
DOI: 10.1007/s10668-019-00404-6
|View full text |Cite
|
Sign up to set email alerts
|

Zootherapeutic uses of animals and their parts: an important element of the traditional knowledge of the Tangsa and Wancho of eastern Arunachal Pradesh, North-East India

Abstract: Using animals and their products to treat patients suffering from a range of health conditions has a long history and is still common in many parts of the world. We investigated such zootherapeutic uses among two tribes who inhabit different areas of NorthEast India: the Tangsa and the Wancho. Overexploitation of the animals they use, however, could endanger some species' survival and create imbalances in the ecosystem that ultimately could affect humans and animals of the region. In order to find solutions ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…On the other hand, poverty pushes population to have recourse to this traditional medicine which is generally available and affordable for all (Rivière et al, 2005;Jugli et al, 2019). Finally, this could explain the inefficiency of modern medicine regarding certain human diseases (Azanlin, 2015;Jugli et al, 2019). The study has also reported 7 mystical practices related to wild mammals identified in the area of study.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…On the other hand, poverty pushes population to have recourse to this traditional medicine which is generally available and affordable for all (Rivière et al, 2005;Jugli et al, 2019). Finally, this could explain the inefficiency of modern medicine regarding certain human diseases (Azanlin, 2015;Jugli et al, 2019). The study has also reported 7 mystical practices related to wild mammals identified in the area of study.…”
Section: Discussionmentioning
confidence: 91%
“…Another important factor is the loss of traditional knowledge related to medicinal animals caused by the lack of interest of young people for this activity. According to Jugli et al (2019), the problem is that traditional healers are often reluctant to share their knowledge and young people are nowadays less and less interested in learning about the "old ways".…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations